Lucy Green, Music, Informal Learning and the School: a New Classroom Pedagogy (2008) - O’Flynn, John (Journal of the Society for Musicology in Ireland, 2010)
Review of Lucy Green, Music, Informal Learning and the School: a New Classroom Pedagogy (Aldershot, UK, and Burlington VT: Ashgate, 2008), ISBN 978-0-7546-6242-6